Konflik Batin Tokoh Utama Dalam Drama Romeo and Juliet dan Drama Atas Nama Cinta - Fitria Amalia; Ramadhan Ramadhan (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
This study aims to analyze two literary works and to present the results of the analyzes that the author has reviewed as a consideration or reference for comparative literary studies with the title